Deep brain stimulation modeling for several anatomical and electrical considerations (2014)
Deep Brain Stimulation (DBS) is a clinical treatment for Parkinson disease symptoms. DBS consists in the implantation of a stimulation electrode into the Subthalamic nucleus (STN) for the excitation of specific regions inside the STN. The stimulation potential has a few parameters that should be adjusted in order to achieve the desired treatment effect. The adjust is performed by the neurologist in several sessions with the patients and is not an exact procedure. In recent years there have been several works on the construction of propagation models of DBS, including head geometries and medium properties in order to visualize the possible effects of DBS while the stimulation parameters are adjusted. This work presents the construction of propagation models using the Finite Element Method (FEM) for the solution of Laplace or Poisson equations that govern the propagation phenomena. By the construction of these models, the shape and magnitude of the electric propagation inside the objective structures can be obtained.